Penggunaan Media Gambar untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPS - Nurita Tri Indaryani; Gunawan Sridiyatmiko (Proceedings Series on Social Sciences & Humanities, 2022)
The problem in this research is: Can using image media in social studies learning improve the learning outcomes of fifth graders at SD Negeri Lugu, Need District, Purworejo Regency. Image media is a form and channel that can be used in a process of presenting information. The problem to be solved in this research is the low learning outcomes of fifth graders at SD Negeri Lugu, Need District, Purworejo Regency, qualitative data and quantitative data, namely, data obtained through teacher and student observation sheets, student observations in cycle I meeting I obtained grades the average was 52.00% and the second meeting increased to 68.25% while in the second cycle the first meeting and second meeting increased by 75.00% and 87.50% overall the value of student activity was in the good category, the results of observations of teacher activities in the first cycle of the first meeting and the second meeting, respectively, namely 53.57% and 64.69, while in the second cycle the first meeting and second meeting increased to 71.43 and 89.39% according to the indicators of the success level of teacher activities already in the category Good. Student learning outcomes obtained after applying image media in social studies learning were classical completeness in the first cycle 20.08% increased to 95.80% in the second cycle and classical absorption obtained in the first cycle was 54.58% to 75.42% in the first cycle. Cycle II from these results it can be concluded that the application of image media can improve student learning outcomes of SD Negeri Lugu, Need District, Purworejo Regency.